Disease burden and associated factors of rotavirus infection in calves in south-eastern part of Bangladesh - Barua, Shama Ranjan; Md Rakib, Tofazzal; Rahman, Mohammad Mahbubur; Selleck, Sarina; Masuduzzaman, Md; Siddiki, AMAM Zonaed; Hossain, Mohammad Alamgir; Chowdhury, Sharmin (Asian Journal of Medical and Biological Research, 2019)
Rotaviruses are considered as a major cause in the etiology of diarrhea in young calves worldwide and it causes calf morbidity, mortality and substantial economic losses in the dairy industry. This study reports the determination of the disease burden and first evaluation of associated risk factors of rotavirus infection in calves in Bangladesh. A cross sectional survey was carried out for the approximation of prevalence and associated risk factors of rotavirus infection in neonatal calves in South-eastern part of Bangladesh. From July 2015 to May 2016 a total of 411 calves under the age of 6 weeks from 210 dairy farms were selected using probability sampling scheme. Rotavirus infection was diagnosed from calf fecal samples using a commercial ELISA kit. Different farm and calf level factors were tested by mixed effect multivariable logistic regression models to differentiate factors significantly contributing to the high burden of rotavirus infection in calves in the study area. Overall prevalence of rotavirus in calf feces, irrespective of diarrheic and non-diarrheic, was estimated as 5.11%. Among the hypothesized risk factors, samples from winter season showed higher odds of having the infection compared to summer (OR=6.04). Likewise, higher odds ratios were observed in: >3 weeks of age group compared to ≤ 3 weeks (OR=2.87), taking of first colostrums after 30 minutes to 2 hours of birth in contrast to within 30 minutes (OR=13.92), and finally, calves from 3rd to 4th parity compared to 1st to 2nd parity (OR=6.79). Enteric diseases are a vital health problem in calves that interrupts production benefits with reduced weight gain and increased mortality rates and moreover it has potential to spread. Therefore, it is imperative to determine the disease burden and responsible risk factors to execute effective preventive measures among the population at higher risk. Asian J. Med. Biol. Res. June 2019, 5(2): 107-116